Machinery, Intelligence and Our Intentionality. Grounds for Establishing Paradoxical Discourses - Colin T. A. Schmidt (tripleC: Communication, Capitalism & Critique)
Attaching the robotic body to the artificial brain (the computer) is a poor way of going about constructing autonomous mentality. It represents nothing more than an extension of the brain and succumbs to using experience as a confirmation of the scientist's belief that he may speak in artificial terms of mind of mentality. This naturally leads to producing a paradoxical discourse on the subject of robotics and thereby leads to confusion. The author indicates readings of paramount importance for disentangling the language involved in this special form of evolutionary computation.